2020
DOI: 10.3389/fimmu.2020.01641
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Influenced Polarization of Activin A-Producing Macrophages Accompanies Post-pyelonephritic Renal Scarring

Abstract: Ascending bacterial pyelonephritis, a form of urinary tract infection (UTI) that can result in hospitalization, sepsis, and other complications, occurs in ∼250,000 US patients annually; uropathogenic Escherichia coli (UPEC) cause a large majority of these infections. Although UTIs are primarily a disease of women, acute pyelonephritis in males is associated with increased mortality and morbidity, including renal scarring, and end-stage renal disease. Preclinical models of UTI have only recently allowed investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 103 publications
3
16
0
Order By: Relevance
“…Instead, these mice fail to limit infection to the kidney parenchyma, exhibiting increased rates of bacterial dissemination and mortality 53 . In the non-refluxing C57BL/6 strain, female mice treated with testosterone also develop persistent kidney infection 52,53,62,63 . These androgenized C57BL/6 females have increased monocyte recruitment, increased M2-polarized macrophages in the kidney from 14 to 28 days post-infection, and increased kidneyassociated M2 macrophage cytokines CXCL1 and CSF-3 from day Fig.…”
Section: Sex Hormones and Uti Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Instead, these mice fail to limit infection to the kidney parenchyma, exhibiting increased rates of bacterial dissemination and mortality 53 . In the non-refluxing C57BL/6 strain, female mice treated with testosterone also develop persistent kidney infection 52,53,62,63 . These androgenized C57BL/6 females have increased monocyte recruitment, increased M2-polarized macrophages in the kidney from 14 to 28 days post-infection, and increased kidneyassociated M2 macrophage cytokines CXCL1 and CSF-3 from day Fig.…”
Section: Sex Hormones and Uti Incidencementioning
confidence: 99%
“…10 to 21 post-infection 63 . Finally, androgen exposure in female mice induces a burst of epithelial-derived TGFβ1 at 24 h postinfection, which polarizes macrophages toward an alternatively activated, pro-fibrotic phenotype, promoting the development of scars surrounded by pro-fibrotic M2a macrophages 62,64 .…”
Section: Sex Hormones and Uti Incidencementioning
confidence: 99%
“…According to our research, there was a significant positive correlation between INHBA expression and macrophage infiltration. Additionally, INHBA has been shown to affect macrophage polarization in vitro Hreha et al (2020) . We hypothesized that INHBA may influence the tumor microenvironment by regulating macrophage polarization, which in turn affects tumor cells.…”
Section: Disscusionmentioning
confidence: 99%
“…It has also recently been reported that androgen exposure can induce macrophages to adopt pro- or anti-inflammatory phenotypes. For example, dihydroxy testosterone exposure can promote M1 macrophage polarization in vitro, while cypionate testosterone treatment can induce an androgen-dependent increase in M2 macrophage polarization in a female mouse infection model [ 60 ]. Evidence also suggests that androgens can regulate oxytocin levels, which have been proposed to attenuate cytokine storms, lymphocyte deficiency, thrombosis, ALI/ARDS and organ failure, leading to its proposed use as a treatment for COVID-19 pathogenesis [ 61 ].…”
Section: Alveolar Cells and Their Roles In Ali/ardsmentioning
confidence: 99%